The New Numerical Galaxy Catalogue (ν2GC): properties of active galactic nuclei and their host galaxies. Issue 4 (1st November 2018) - Shirakata, Hikari; Okamoto, Takashi; Kawaguchi, Toshihiro; Nagashima, Masahiro; Ishiyama, Tomoaki; Makiya, Ryu; Kobayashi, Masakazu A R; Enoki, Motohiro; Oogi, Taira; Okoshi, Katsuya
ABSTRACT: We present the latest results of a semi-analytic galaxy formation model, ' New Numerical Galaxy Catalogue ', which utilizes large cosmological N -body simulations. This model can reproduce many statistical properties of galaxies at z  ≲ 6. We focus on the properties of active galactic nuclei (AGNs) and supermassive black holes, especially on the accretion time-scale on to black holes (BHs). We find that the number density of AGNs at z < 1.5 and at hard X-ray luminosity <10 44 erg s −1 is underestimated compared with recent observational estimates when we assume the exponentially decreasing accretion rate and the accretion time-scale which is proportional to the dynamical time of the host halo or the bulge, as is often assumed in semi-analytic models. We show that to solve this discrepancy, the accretion time-scale of such less luminous AGNs should be a function of the BH mass and the accreted gas mass. This time-scale can be obtained from a phenomenological modelling of the gas angular momentum loss in the circumnuclear torus and/or the accretion disc. Such models predict a longer accretion time-scale for less luminous AGNs at z < 1.0 than luminous QSOs whose accretion time-scale would be 10 7–8 yr. With this newly introduced accretion time-scale, our model can explain the observed luminosity functions of AGNs at z < 6.0.